2011
DOI: 10.1016/j.jmb.2011.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Chlorite Dismutases, DyPs, and EfeB: 3 Microbial Heme Enzyme Families Comprise the CDE Structural Superfamily

Abstract: Heme proteins are extremely diverse, widespread, and versatile biocatalysts, sensors, and molecular transporters. The chlorite dismutase family of hemoproteins received its name due to the ability of the first-isolated members to detoxify anthropogenic ClO 2 − , a function believed to have evolved only in the last few decades. Family members have since been found in fifteen bacterial and archaeal genera, suggesting ancient roots. A structure-and sequence-based examination of the family is presented, in which k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
129
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(131 citation statements)
references
References 57 publications
2
129
0
Order By: Relevance
“…It has been reported that acidic side chains in the vicinity of a tryptophan or a tyrosine stabilize an emerging radical cation (26,47,48). Alignments with other DyPs show that Tyr-337 is a conserved residue in fungal as well as bacterial DyPs and the related enzymes TyrA from Shewanella oneidensis and EfeB from Escherichia coli but is missing in Cld-like proteins (5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that acidic side chains in the vicinity of a tryptophan or a tyrosine stabilize an emerging radical cation (26,47,48). Alignments with other DyPs show that Tyr-337 is a conserved residue in fungal as well as bacterial DyPs and the related enzymes TyrA from Shewanella oneidensis and EfeB from Escherichia coli but is missing in Cld-like proteins (5).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, a new family of enzymes was established to accommodate these unusual peroxidases (4). From a structural viewpoint, DyPs are best considered members of a highly diverse superfamily of proteins comprising, among others, Clds and DyPs, sharing a ferredoxin-like core of ␤-sheets as a common feature (5). Actually, even the term "DyP" circumscribes a polyphyletic group that can be roughly divided into four different entities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SaHemQ is representative of a large subgroup of Cld-family proteins, including all Clds from phylum Firmicutes, which have a conserved glutamine residue at the position of a distal Arg that we have observed is critical for efficient reactivity with anionic oxidants (1,3,8). Unlike typical peroxidases, Clds likewise lack a distal base and other residues important for stabilizing polar reaction intermediates ( Fig.…”
mentioning
confidence: 90%
“…The peroxidase-chlorite dismutase superfamily (CDE structural superfamily) comprises chlorite dismutases (Clds), chlorite dismutase-like (Cld-like) proteins (HemQs in Gram-positive bacteria) and dye-decolourizing peroxidases (DyPs) [1,2]. Although distinct enzymatic reactions can be assigned to Clds (degradation of chlorite to chloride and dioxygen) and DyPs (H 2 O 2 -mediated one-electron oxidation reactions of various aromatic compounds), knowledge about the biochemical and physiological function of Cld-like proteins is only fragmentary at present.…”
Section: Introductionmentioning
confidence: 99%